On the road towards progress? - Dieter W. Vogelsang (Intereconomics, 1971)
A decisive new era of development opens for India. It will be largely for a woman, Indira Gandhi, whose triumph In the March elections for the central parliament was acclaimed so enthusiastically, to give it her imprint.
Keywords: 330; India